Métodos não-letais de coleta de amostras para o diagnóstico de infeccção por Streptococcus agalactiae em Tilápia do Nilo (Oreochromis niloticus) - Guilherme Campos Tavares (2014)
Streptococcus agalactiae has emerged as a major etiological agent of septicemia and meningoencephalitis outbreaks in fish farms around the world. In Brazil, this microorganism is a major health threat for Nile tilapia farms. The aim of this study was to standardize nonlethal sampling methods to diagnose infections caused by S. agalactiae in Nile tilapia, by microbiological and molecular tests. Therefore, the study was divided into two stages. The first step consisted in standardization of nonlethal sampling methods (kidney needle biopsy and venipuncture) in Nile tilapia. The second step consisted in infection experimental in Nile tilapia with Streptococcus agalactiae SA 20-06 and clinical sensitivity in bacteriological and PCR methods were measured from nonlethal and lethal sampling methods. There was statistically significant difference between lethal and nonlethal methods for detection of pathogen for both diagnostic methods. Diagnostic frequency was significantly greater for bacteria in brain samples detection compared with other samples obtained in present study, regardless of diagnostic method. Sample collection methods and diagnosis were effective for detecting sick fish and carrier. There was no statistically significant difference between bacteriology and PCR for diagnosis of S. agalactiae from brain samples. Results suggest that kidney needle biopsy and venipuncture can be used as nonlethal sampling methods for detection of S. agalactiae in Nile tilapia, but with less that brain bacteriology results.